Towards new commons and sharing interests in the landscape, integrating natural and cultural heritage - Pedroli, Bas (Ex Novo: Journal of Archaeology, 2019)
Heritage values represent a common good, contributing to societal identity. Landscape is a topical issue because it represents character and identity in both a spatial and a temporal dimension, uniting natural and cultural aspects of heritage at the same time. Especially in Europe, practically all natural heritage can be considered cultural heritage as well, since it is through human action that Europe’s biodiversity has evolved. Heritage perspectives on landscape and nature underline time depth, human agency and social value within landscape. Its cultural starting point does not marginalise nature, but places nature within cultural filters, thus highlighting the reciprocity of nature and culture in the creation of sustainable places. Today’s changing society is transitioning towards new forms of governance dominated by collaboration and continuously shifting networks or actors. Reported examples of cultural landscapes explore heritage management approaches that benefit from combining natural and cultural heritage perceptions. In this context, commonly accessible heritage can bring people together in joint efforts to use the inherited landscape as a shared and cherished resource rather than a conserved and regulated landscape.